Diagnosis and Management of Narcolepsy Reviewed - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Researchers at Duke University Medical Center, and Veterans Affairs Medical Center, Durham, NC, review the epidemiology, pathophysiology, diagnosis, and treatment of pediatric narcolepsy.